2022
DOI: 10.3389/fpubh.2022.995755
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical activity dimensions and the risk of hypertension among middle and older adults: A cross-sectional study in China

Abstract: BackgroundIt is known that insufficient physical activity is associated with the risk of hypertension, but the relationship to different physical activity dimensions within hypertension risk remains to be elucidated.ObjectiveThe objective of this study is to identify the association between physical activity intensity, frequency, duration, and volume with hypertension risk. Meanwhile, a dose-response experiment is conducted to determine the relationship between physical activity level and hypertension risk.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Many researches have demonstrated that several risks are linked to hypertension, including obesity, consumption of alcoholic beverages, sodium, homocysteine and vitamin intake (6)(7)(8). Homocysteine, an amino acid containing sulfur, is produced via the metabolic pathways of methionine, an essential amino acid obtained from dietary proteins (9).…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have demonstrated that several risks are linked to hypertension, including obesity, consumption of alcoholic beverages, sodium, homocysteine and vitamin intake (6)(7)(8). Homocysteine, an amino acid containing sulfur, is produced via the metabolic pathways of methionine, an essential amino acid obtained from dietary proteins (9).…”
Section: Introductionmentioning
confidence: 99%